PERUBAHAN TUTUPAN LAHAN DAN PENGARUHNYA TERHADAP KEJADIAN BANJIR DI WILAYAH PROVINSI DKI JAKARTA - Adnan, Farhandani
Land cover changes in watersheds tend to increase in intensity according to space and time and negatively affect the quality of watershed land, including increased peak discharge, surface runoff coefficient, and flooding. To monitor patterns of land cover changes that occur rapidly, remote sensing technology is used, based on spatial data of satellite imagery. The purpose of this study is to identify the effect of changes in land cover on flood events in DKI Jakarta Province. The study was conducted in March - June 2020 at the School of Urban Planning, Bandung Institute of Technology. The pattern of changes in land cover in watersheds tends to increase in the upstream, especially the Ciliwung and Cisadane watersheds with a percentage of 10-20% during the study period. In 2018 Ciliwung watershed 53% of the land has been dominated by developed land, Krukut watershed 85%, Sunter watershed 78%, Angke watershed 70%, Buaran watershed 90%, Cakung watershed 72%, and Cisadane watershed 23%. Constructed land tends to convert agricultural land and water bodies, whereas agricultural land converts forest land. The amount of vegetated land turned into non-vegetated land has resulted in an increase in flowrate and runoff coefficient. It is known that in 2018 the watersheds that have the highest value for runoff coefficient are Buaran Watershed (0.86), Krukut Watershed (0.84) and Angke Watershed (0.78).